Regional transient portal ischemia and irradiation as preparative regimen for hepatocyte transplantation - König, Sarah; Yuan, Q.; Krause, P.; Christiansen, H.; Rave-Fraenk, M.; Kafert-Kasting, S.; Kriegbaum, H.; Schneider, A.; Ott, M.; Meyburg, Jochen (Cell transplantation, 2011)
Hepatocyte transplantation is regarded as a promising option to correct hereditary metabolic liver disease. This study describes a novel method involving regional transient portal ischemia (RTPI) in combination with hepatic irradiation (IR) as a preparative regimen for hepatocyte transplantation. The right lobules of rat livers (45% of liver mass) were subjected to RTPI of 30-120 min. Liver specimens and serum samples were analyzed for transaminase levels, DNA damage, apoptosis, and proliferation. Repopulation experiments involved livers of dipeptidylpeptidase IV (DPPIV)-deficient rats preconditioned with RTPI (60-90 min) either with or without prior partial hepatic IR (25 Gy). After reperfusion intervals of 1 and 24 h, 12 million wild-type (DPPIV positive) hepatocytes were transplanted into recipient livers via the spleen. RTPI of 60-90 min caused limited hepatic injury through necrosis and induced a distinct regenerative response in the host liver. Twelve weeks following transplantation, small clusters of donor hepatocytes were detected within the portal areas. Quantitative analysis revealed limited engraftment of 0.79% to 2.95%, whereas control animals (sham OP) exhibited 4.16% (determined as relative activity of DPPIV when compared to wild-type liver). Repopulation was significantly enhanced (21.43%) when IR was performed prior to RTPI, optimum preconditioning settings being 90 min of ischemia and 1 h of reperfusion before transplantation. We demonstrate that RTPI alone is disadvantageous to donor cell engraftment, whereas the combination of IR with RTPI comprises an effective preparative regimen for liver repopulation. The method described clearly has potential for clinical application.
Gesehen am 06.07.2022